Determination of the Chemical Properties of Honey from Suba Region, Homa Bay County-Kenya - Ondogo, Linet; Oyoo, Daniel; Bichanga, Robert (International Journal of Food Sciences, 2023)
Purpose: The purpose of this study was to determine the chemical properties of honey produced in the Suba region, specifically in the Suba South Sub-County, Gwassi North and South divisions' four regions, Nyandiwa (Western), Tonga (Northern), Magunga (Eastern), and Nyancha (Central) of Homa Bay County, Kenya. The study focuses on assessing the chemical properties of honey such as pH, free acidity, HMF content, proline content, glucose content, fructose content, sucrose content and mineral concentrations (K,Na,Ca,Mg,Fe,Zn,and Mn) to ascertain whether they are within the acceptable limits as set by the Codex Alimentarius Commissions. Methodology: An experimental approach was used to investigate the various chemical properties of honey sourced from the four regions of the Suba region in Homa Bay County. Codex Alimentarius Commission's defined methods were used to analyze each property. Both primary and secondary data were collected using interviews and purposive sampling techniques to collect a total of 40 honey samples. A pH meter, UV-visible spectrophotometer, and HPLC instruments were used to measure the pH, free acidity, HMF content, proline content, fructose content, glucose content, and sucrose content of the honey, respectively. The levels of minerals were measured using AAS for Na and K, while Ca, Zn, Mg, Mn, and Fe using a flame photometer. Statistical Package for Social Sciences version 21 was used to perform various statistical tests and generate graphical representations of data. The collected samples were analysed at the Kenyatta University Research Laboratory. Findings: The findings showed that the chemical properties had the following mean values for the honey sample: pH = 4.01± 0.03, free acidity = 35.83±0.45 mEq/kg, HMF = 19.95±1.76 mg/kg, proline = 629.77±9.80 mg/kg, sum of glucose and fructose = 68.37±0.51%. While for the minerals, manganese was the least common and potassium the most common. The mean values result of this study show that honey from the Suba region satisfies the set standards by Codex Alimentarius Commission. Unique Contribution to Theory, Practice and Policy: The study validates the theory of international standards in honey production, emphasizing the positive impact of aligning with global benchmarks on honey quality and market acceptance in the Suba region. It emphasizes the importance of quality certification, which contributes to consumer trust and economic growth. The research also supports the theory through sensitization and education, which increase awareness about honey quality and educate beekeepers on proper production techniques. The study advocates for economic diversification through sustainable apiculture, resulting in improvements in economic stability and financial well-being in the Suba region.